Process optimization of spray‐dried Moldavian balm (Dracocephalum moldavica L.) extract powder. Issue 12 (18th November 2020) - Rahmati, Edris; Sharifian, Faroogh; Fattahi, Mohammad
Abstract: The present study was aimed to develop the powder from Moldavian balm extract using a spray dryer to preserve the valuable phytochemicals such as hydroxycinnamic acid and flavonoids. In order to produce optimum Moldavian balm spray‐dried powder, response surface methodology was applied. The inlet air temperature (120–180°C), compressed airflow rate (5–10 L/min), and carriers' concentration (10%–30%) were kept as independent variables, while moisture content, drying performance, porosity, total phenol content, total flavonoid content, and antioxidant activity were selected as responses. The process was optimized with inlet air temperature of 140.36°C, compressed airflow rate of 9.13 L/min and carriers' concentration of 18%, resulting in powder with moisture content of 7.68%, drying performance of 62.52%, porosity of 76.4%, total phenol content of 6.295 mg GAE/g, total flavonoid content of 0.378 mg QUE/g, and antioxidant activity of 51.78%. The optimized process led to attain the powder having significantly better phytochemical properties compared with others. Abstract : A powder from Moldavian balm plant extract successfully obtained using spray‐drying. Air temperature, airflow, and carriers were experimental independent variables. Optimum conditions of variables were 140.36°C, 9.13 L/min, and 18%, respectively. Spray‐dried optimized powder retained significant amount of phytochemical compounds.